2013
DOI: 10.1590/1516-4446-2013-1131
|View full text |Cite
|
Sign up to set email alerts
|

Have drivers at alcohol outlets changed their behavior after the new traffic law?

Abstract: Objective: In an attempt to reduce high levels of traffic crashes, a new legislation was approved in Brazil in 2008. This study aimed to assess behavioral change among drivers who had drunk at alcohol outlets (AO) after implementation of the law. Method: A three-stage probability sampling survey was conducted in Porto Alegre, state of Rio Grande do Sul, Brazil. Individuals seen leaving AOs after drinking were approached (n=3,018). Selected drivers (n=683) answered a structured interview, were breathalyzed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Although there was a nationwide decrease, pedestrians remain the main victims of RTI. Brazil has relatively strong national legislation on key aspects of road safety, but a reasonable doubt emerges about its enforcement, especially related to drinking and driving laws [ 62 , 63 ]. Numbers of motorcyclist road injury deaths increased the most from 1990 to 2015, probably linked to a high rise in the use of this kind of vehicle [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there was a nationwide decrease, pedestrians remain the main victims of RTI. Brazil has relatively strong national legislation on key aspects of road safety, but a reasonable doubt emerges about its enforcement, especially related to drinking and driving laws [ 62 , 63 ]. Numbers of motorcyclist road injury deaths increased the most from 1990 to 2015, probably linked to a high rise in the use of this kind of vehicle [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that drinking and driving is not associated with fear of punishment but rather with being male, binge drinking, having had a driving under the influence-related crash in the past, or having a negative perception of driving under the influence policy Pinsky et al 2001). Additionally, though drink driving is associated with consumption at alcohol outlets such as bars/pubs, restaurants, nightclubs, and convenience stores, the nature of this association may vary based on the density of these outlets; for instance, low-density areas may actually be where people are more likely to drink and drive (Boni et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol affects all tissues and has a significant impact on the nervous system. 28 The CBT Brazilian Traffic Code amendments, through Law No. 12,760/2012, propose penalties to the individuals driving with any alcohol concentration per liter of blood or alveolar air 29 .…”
Section: Discussionmentioning
confidence: 99%
“…However, 60.3% of drivers have not yet changed their behavior after the introduction of this new law. 28 Concerning motorcyclists, the students described the very dangerous maneuver of balancing the motorcycle on one wheel in their drawings. In Article 175, the CTB considers the use of a vehicle to demonstrate or perform dangerous maneuvering, such as sudden jerking, skidding, or braking with tire sliding or dragging, a serious violation.…”
Section: Discussionmentioning
confidence: 99%